THE PHYSICS TEACHER'S TRAINING TO PLANNING INFORMATIVELY EDUCATIONAL ENVIRONMENTS. - O. Borovik (Kherson State University, 2010)
It is examined questions, related to the studies of physics teachers to planning of educational environments in postgraduate education system, in the article